Nationale Identität im Wandel : Erscheinungsformen des albanischen Nationalismus - Myteveli, Valbona (Albanische Forschungen, 2018)
At the end of the 19th century, the idea of ​​uniting all Albanians in a common state emerged. In this process of national emancipation, different facets of Albanian nationalism have emerged in Albania, Kosovo and Macedonia. The resulting rivalry between the political forces characterizes the political culture to this day. Taking into account the role that the interaction of subjective criteria such as language, history and religion play in the formation of national identity, Valbona Myteveli examines in her study the linguistic, historical and denominational characteristics that are considered the foundation of Albanian national consciousness. Since the development of Albanian nationalism includes both defensive and offensive nationalist elements, political decisions are examined that not only aim to consolidate national identity and state structures, but also to transform the existing value system out of power-political calculations. In addition, the role of external actors who have continuously shaped the political development of the Albanian community is also considered. Myteveli's research concludes with the question of whether the integration of these countries into the European Union is still a viable option for the future and whether this integration can neutralize the nationalist tendencies in Albania, Kosovo and Macedonia.